Institusionalisasi Partai Keadilan Sejahtera (PKS) dan Partai Persatuan Pembangunan (PPP) di Kota Palembang - Putra, Agung Pratama; Norhuda, Norhuda; Adytyas, Nico Oktario (Ampera: A Research Journal on Politics and Islamic Civilization, 2021)
This research is entitled "INSTITUTIONALIZATION OF ISLAMIC POLITICAL PARTIES IN PALEMBANG CITY: A Case Study of the Prosperous Justice Party (PKS) and the United Development Party (PPP)". This research explains that the institutionalization of Islamic political parties in Palembang City can affect the results of the legislative elections and the existence of voters, which at the time of the 2019 legislative elections in Palembang City, the votes and seats of Islamic political parties experienced very significant changes in terms of the number of votes. and legislative seats. Islamic political parties that experienced an increase in the number of votes and legislative seats, namely the Prosperous Justice Party (PKS) when the 2014 legislative general election received three seats but in the 2019 legislative general election it got five seats, while the Islamic political parties which experienced a decrease in the number of votes and legislative seats, namely the Party The Development Association (PPP) when the 2014 legislative election won two seats, but in the 2019 legislative general election, it only got one seat. The reason the author chose the title Institutionalization of Islamic Political Parties in Palembang City is due to the extent to which Islamic parties have or have not been institutionalized, this research on the institutionalization of political parties uses the theory of Vicky Randall and Lars Svasand political parties are considered institutionalized if there are four degrees of institutionalization such as Degree of System, Degree of Value Identity , Degree of Decision Autonomy and Degree of Public Knowledge. Based on the theory used, the results of this study, among others, prove that PKS can be said to have been institutionalized and PPP has not been institutionalized based on the four degrees of political party institutionalization theory concept according to Vicky Randall and Lars Svasand. So that it can be directly proven by the results of research findings where the institutionalization of PKS and PPP parties has similarities and differences between the two Islamic political parties in absorbing the people's aspirations and fighting for the interests of Muslims in Palembang City.